'MINUSTAH is doing positive things just as they do negative things': nuanced perceptions of a UN peacekeeping operation amidst peacekeeper-perpetrated sexual exploitation and abuse in Haiti. Issue 6 (2nd November 2021) - King, Carla; Ferraro, Greg; Wisner, Sandra C.; Etienne, Stéphanie; Lee, Sabine; Bartels, Susan A.
ABSTRACT: Haiti's instability at the turn of the millennium demanded unprecedented changes towards community-based peacekeeping strategies. While deemed successful by some in reducing actualised violence, the UN Peace Support Operation, MINUSTAH, was wrought with allegations of sexual exploitation and abuse (SEA) and mired by the inadvertent introduction of cholera. To understand the host community's experiences with MINUSTAH, data was collected around seven UN bases from 10 locations in Haiti between June and August 2017. We find that Haitian perceptions on reporting, justice and responsibility for SEA are in juxtaposition with MINUSTAH's efforts towards stabilisation and security. While participants identified positive perceptions of MINUSTAH that aligned with the novel community violence reduction strategy employed in Haiti, outstanding concerns around SEA remain. We recommend the UN addresses its environment of impunity, alters its practices and policies to be victim/survivor-centred and improve transparency and communication with host communities. The UN must make the systemic changes necessary to address impunity or provide reparations for peacekeeper-perpetrated SEA.